Role of Physiotherapy on Quality of Life in Stroke Survivors – A Systematic Review - Kanase Suraj B1, G.Varadharajulu2, Pragati V. Salunkhe3, Mayuri D.Burungale3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Stroke is one of the most common disease with lots of impairments and disabilities. Prevalence of stroke is increasing day by day globally. Young stroke is becoming very common. The overall functional capacity of the individual is hampered where the prognosis is question mark. It largely depends upon site, stage, duration of lesion. The overall quality of function is deteriorated. Patients live their lives with dependency. According to previous studies, role of various health care professionals have been analyzed and studied. Physiotherapy is a branch where use of exercise and electrotherapy plays their role in rehabilitating patients with stroke Aim: To study the role of physiotherapy on quality of life in stroke survivors. Methodology: A systematic narrative review was conducted to find out the efficacy of physiotherapy treatment on quality of life in stroke survivors. Conclusion: Stroke has complex process of recovery. Stroke survivors are left with disabilities. It causes depression in patients as well as their family members. Physiotherapy has a significant role in improving impairments and disabilities. This in turn helps in improving quality of life